The Importance of Teachers Implementing Social Emotional Learning for Students in The Era of Generation Z - Prama Wati, Ni Putu Eka; Asli, Luh (International Journal of Multidisciplinary Sciences, 2024)
Generation Z was born and grew up in the digital era, this generation is expert in using smartphones, social media and the internet. Without proper supervision, this generation will face various negative impacts including mental disorders, technology addiction, cyberbullying, stress and unhealthy lifestyles. With the phenomena experienced by our generation today, it is a challenge as a teacher to minimize the negative impacts. One of the efforts is through the application of Social Emotional Learning. Through this PSE, it is hoped that students will feel safe and comfortable in learning. This research aims to find out the extent to which teachers have implemented Social Emotional Learning with their students and the importance of teachers implementing Social Emotional Learning. Through qualitative research, data was obtained by conducting interviews and document studies. The research results show that teachers can apply Social Emotional Learning both explicitly such as co-curricular and extra-curricular activities and integrated into teachers' teaching practices. Social awareness and relationship skills can be developed through group learning activities and discussions, students will learn how to respect and appreciate the opinions of their friends, growing concern between friends by experiencing what their friends are experiencing. The teacher conveys steps for effective communication in groups to solve problems without conflict, by applying the I-massage technique, which focuses on the feelings of conveying the message, not the thoughts or characteristics of the person speaking. PSE is a learning process related to self-awareness, self-management and social awareness. By implementing PSE, students will have empathy for other people and be able to interact and communicate effectively.